Curved grooves at the Godzilla Megamullion in the Philippine Sea and their tectonic significance. Issue 6 (10th June 2014) - Spencer, Jon E.; Ohara, Yasuhiko
Abstract Deep‐sea core complexes are characterized by remarkably well developed grooves that formed below extensional detachment faults and reveal plate‐divergence direction during asymmetric plate spreading. The Godzilla Megamullion in the Parece Vela Basin in the Philippine Sea contains the longest known grooves on an oceanic core complex, with individual groove lengths up to 60 km. Over much of the complex, curved grooves reveal a 10° change in plate‐divergence direction during Miocene back arc spreading behind the Mariana island arc. Evaluation of groove and transform‐fault orientations indicates that the curved grooves do not reflect plate displacement about a fixed pole of rotation, but rather reflect a change in the position of the rotation pole. This in turn was associated with increasingly significant left‐lateral transform motion in the back‐arc Parece Vela Basin.